A comparative study of prepared Bhasma using different marine-originated animal materials: Nallaperuma D.M.*, Herapathdeniya S.K.M.K. and Senaviratne A.M.N.D. (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2025)
Rasa shastra is a main pharmaceutical branch in Ayurveda and Mercury is the main material in Rasa shastra. Other than mercury, different animal resources, minerals, gems, marine originated materials and some toxic plants are also described under Rasa shastra. Shankha, Shukthi and Kaparda are some of the commonly used marine originated animal materials. These materials contain Calcium and categorized under Sudha varga. The objective of this study is to prepare Shankha, Shukthi and Kaparda bhashmas according to Rasa shastra and to comparatively analyze the physico-chemical parameters and to determine the Calcium content of these Bhashmas. Boiling and steaming method was used for the purification, and incineration was done by using the muffle furnace at 550°C. Bhashma standardization parameters in Rasa Shastra; Rekha purnatva, Varitharathva, Uththama, Gatha rasathva, Avami, Anjana sadrusha sukshma and Dantagra na kacha kacha were performed for all these bhashmas. Calcium percentage in each bhashma was determined by titrating with 0.1M NaOH solution using phenolphthalein as the indicator. Results revealed that all the Bhashmas were within the standard parameters according to classical texts. According to modern physico-chemical analysis, moisture contents of all the samples were relatively low (0.40%, 1.30%, 0.95%). Total ash contents were 99.20%, 98.50% and 98% respectively. Acid insoluble ash values (52%, 77.80%, 57%) were higher than water soluble ash values (3.80%, 2.60%, 1.65%). All the samples were having an alkaline pH value (8.2, 8.0, 8.7). The highest calcium percentage was reported from Shukthi bhashma (99.30%) and lowest from Kaparda bhashma (78.40%). It can be concluded that all the Bhashmas were having the standard quality according to Ayurveda as well as modern physicochemical parameters. Due to the high calcium content, Shukthi bhashma can be highly recommended as a nutritional supplement for Calcium deficiencies among these Bhashmas. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;"><br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">